Narrative Sermon on the Good Samaritan (Luke 10:25-37) - King, Rosemary (The expository times, 2007)
The article presents a narrative sermon regarding a good Samaritan based on the Gospel of Luke chapter 10 verses 25 to 37. It says that a man named Daniel Levin approached Jesus Christ and asked what he needs to do to have a share in eternal life which is being discussed by Jesus in a crowd. It says that Jesus emphasized the importance of loving God with heart, mind, soul and strength.